Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Find the point(s) on the ellipse: x²/a² + (y - k)/b² = 1 where the tangent line that passes through the point: (m, n)?
Find the point(s) on the ellipse:
x²/a² + (y - k)/b² = 1
where the tangent line passes through the point:
(m, n)
I forgot the square of (y - k)...
the ellipse is:
x²/a² + (y - k)²/b² = 1
1 Answer
- RogueLv 76 years ago
first x²/a² + (y − k)/b² = 1 is a parabola not an ellipse so let's assume you meant x²/a² + (y − k)²/b² = 1
x²/a² + (y − k)²/b² = 1
∴ d/dx(x²/a² + (y − k)²/b²) = d/dx(1)
∴ d/dx(x²/a²) + d/dx((y − k)²/b²) = d/dx(1)
∴ (1/a²)d/dx(x²) + (1/b²)d/dx((y − k)²) = d/dx(1)
∴ (1/a²)d/dx(x²) + (2/b²)(y − k) * d/dx(y − k) = d/dx(1)
∴ (1/a²)d/dx(x²) + (2/b²)(y − k)(d/dx(y) − d/dx(k)) = d/dx(1)
∴ 2x/a² + (2/b²)(y − k)(dy/dx − 0) = 0
∴ (2/b²)(y − k)(dy/dx) = - 2x/a²
∴ dy/dx = -b²x/(a²(y − k))
∴ dy/dx = b²x/(a²(k − y))
given a tangent line at (x₁,y₁) is equal (y − y₁) = (dy/dx)(x − x₁)
so at (n,m) it is (y − n) = (b²m/(a²(k − n)))(x − m)
∴ y = b²m(x − m)/(a²(k − n))) + n